2023
DOI: 10.5551/jat.63856
|View full text |Cite
|
Sign up to set email alerts
|

Angiographic Coronary Calcification: A Simple Predictor of Long-Term Clinical Outcomes in Patients with Acute Myocardial Infarction

Abstract: Aims: Coronary calcification detected by coronary angiography is a simple risk marker for long-term clinical outcomes in stable coronary artery disease. However, the significance of angiographic coronary calcification in the culprit lesion of acute myocardial infarction (AMI) has not been fully discussed. The purpose of this retrospective study was to assess the usefulness of angiographic coronary calcification as a risk marker for longterm clinical outcomes following percutaneous coronary intervention to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The relationship between the presence of OCT-CN and heart failure remains unclear. Previous studies reported relationships between higher Killip class and a higher prevalence of diabetes, 24,25 3-vessel disease, 24 and angiographic coronary artery calcification, 26 indicating the presence of advanced atherosclerosis. Because OCT-CN is accompanied by underlying calcified plaque, advanced Killip class may be an indicator of OCT-CN.…”
Section: Clinical Predictors Of Oct-cnmentioning
confidence: 89%
“…The relationship between the presence of OCT-CN and heart failure remains unclear. Previous studies reported relationships between higher Killip class and a higher prevalence of diabetes, 24,25 3-vessel disease, 24 and angiographic coronary artery calcification, 26 indicating the presence of advanced atherosclerosis. Because OCT-CN is accompanied by underlying calcified plaque, advanced Killip class may be an indicator of OCT-CN.…”
Section: Clinical Predictors Of Oct-cnmentioning
confidence: 89%
“…The association of vascular and valve calcifications with the clinical outcomes of AMI has been the subject of several studies [ 2 , 5 , 15 17 ]. However, no previous study had explored the relationship between the cumulative calcification score (including CAC, TAC, and AVC) and the prognosis of STEMI.…”
Section: Discussionmentioning
confidence: 99%